Female Testaments as Social Discourse: A Textual Analysis Under a Critical Discourse Analysis Approach - Mira, MarÃa Isabel MartÃnez (Mediterranean Journal of Social Sciences, 2011)
The following article is an analysis of 33 female wills (from 16th-20th centuries) found in notarial protocols at the MurciaRegional Archives (Murcia, Spain). Using a Critical Discourse Analysis framework, with special emphasis of Pierre Bourdieu’spostulates, this article studies how women handle gender, cultural, and power relations, challenge social hierarchies and, at the same time,reproduce them in their attempt to look respectable/honorable, assert their power, redefine themselves and negotiate their public image.